MEMBANGUN LOYALITAS BRAND MELALUI STORYTELLING DI MEDIA SOSIAL DI SMA PGRI 2 DEPOK - Farisah Anggraini; Ahmad Rizal; Safannah Muslimatin Rinahandahani (LAP4B, 2026)
This Community Service Program (PKM) was conducted at SMA PGRI 2 Depok with the aim of providing students with an understanding of the importance of storytelling strategies in building brand loyalty through social media. The rapid development of social media has made the ability to create engaging and communicative content one of the essential skills in the digital era. Through this program, participants were educated on the concepts of branding, consumer loyalty, and effective storytelling techniques in digital content creation.